Performing Sufi Masculinity by Transcending Embodiment in Ibn ʿAṭāʾ Allāh’s Kitāb al-Ḥikam - Deighton, Rose (Journal of Islamic ethics, 2020)
Abstract Through a gendered analysis of Ibn ʿAṭāʾ Allāh’s (d. 709/1309) Kitāb al-Ḥikam (“Book of Wisdom”) this paper demonstrates how the Sufi program offered in the Ḥikam prescribes the performance of masculinity through the transcendence of embodiment. Reading the text’s only reference to women as an occurrence of what Jacques Derrida calls textual self-reference, this essay explores how this statement functions as a key to the text’s gender discourse. The explicit reference, supported by evidence from Ibn ʿAṭāʾ Allāh’s other writings, mirrors the theory of embodiment and gender reflected through the text. This essay illuminates how conceptual descriptions of Sufi spirituality meant to reinforce the importance of transcending embodiment take on gendered meaning when read against explicit comparisons between women, the nafs and the dunyā . This paper highlights ways in which Ibn ʿAṭāʾ Allāh’s spiritual instructions encourage the performance of masculinity through the transcendence of embodiment, thus prompting conversations about spiritual cultivation’s groundedness in and reinforcement of normative gender discourses.